IMPLEMENTASI KEBIJAKAN PENDIDIKAN INKLUSIF MELALUI TRANSFORMASI MANAJEMEN SEKOLAH - Fatmawati, Fatmawati (Universitas Tanjungpura, 2025)
The principle of inclusive education policy is to integrate students with special needs into the general education environment. This study aims to describe the implementation of inclusive education policy through school management transformation at SMA Negeri 3 Sanggau. The school management components studied focus on student management, curriculum, and the learning process. This research uses a descriptive qualitative approach. Interviews, observations, and documentation activities were conducted to collect data. Data sources include school principals, educators, and students. Data analysis uses the interactive model of Miles and Huberman.Based on the research results, the transformation of student management consists of several stages, namely preparation, identification, and assessment during new student admissions. The transformation of curriculum management involves the development and use of the Kurikulum Merdeka (Independent Curriculum), adapted with an inclusive adaptive curriculum using a duplication model. Furthermore, the transformation of learning process management at SMA Negeri 3 Sanggau includes: Preparation of learning tools, which covers learning achievement analysis, learning objectives, learning objectives flow, lesson plans (RPP), or teaching modules,Implementation of classroom teaching and learning activities, and Assessment.The conclusion is that the implementation of inclusive education policy has been pursued through school management transformation; however, it still requires support from all stakeholders so that SMA Negeri 3 can implement inclusive education more optimally. Recommendations for school principals include consistently striving to establish collaboration and communication with relevant parties, and for teachers to continually update their knowledge regarding inclusive education